Concordant Cues in Faces and Voices: Testing the Backup Signal Hypothesis. (24th February 2016) - Smith, Harriet M. J.; Dunn, Andrew K.; Baguley, Thom; Stacey, Paula C.
Information from faces and voices combines to provide multimodal signals about a person. Faces and voices may offer redundant, overlapping (backup signals), or complementary information (multiple messages). This article reports two experiments which investigated the extent to which faces and voices deliver concordant information about dimensions of fitness and quality. In Experiment 1, participants rated faces and voices on scales for masculinity/femininity, age, health, height, and weight. The results showed that people make similar judgments from faces and voices, with particularly strong correlations for masculinity/femininity, health, and height. If, as these results suggest, faces and voices constitute backup signals for various dimensions, it is hypothetically possible that people would be able to accurately match novel faces and voices for identity. However, previous investigations into novel face–voice matching offer contradictory results. In Experiment 2, participants saw a face and heard a voice and were required to decide whether the face and voice belonged to the same person. Matching accuracy was significantly above chance level, suggesting that judgments made independently from faces and voices are sufficiently similar that people can match the two. Both sets of results were analyzed using multilevel modeling and are interpreted as being consistent with the backup signal hypothesis.